Thermal conductivity and dynamic viscosity of highly mineralized water (2022)
Further development in the field of geothermal energy require reliable reference data on the thermophysical properties of geothermal waters, namely, on the thermal conductivity and viscosity of aqueous salt solutions at temperatures of 293–473 K, pressures Ps = 100 MPa, and concentrations of 0–25 wt.%. Given the lack of data and models, especially for the dynamic viscosity of aqueous salt solutions at a pressure of above 40 MPa, generalized formulas are presented here, by which these gaps can be filled. The article presents a generalized formula for obtaining reliable data on the thermal conductivity of water aqueous solutions of salts for Ps = 100 MPa, temperatures of 293–473 K and concentrations of 0%–25% (wt.%), as well as generalized formulas for the dynamic viscosity of water up to pressures of 500 MPa and aqueous solutions of salts for Ps = 100 MPa, temperatures 333–473 K, and concentration 0%–25%. The obtained values agree with the experimental data within 1.6%.